Nilai-nilai Moderasi Beragama dalam Tradisi Syukur Panen Masyarakat Dayak Aoheng di Provinsi Kalimantan Timur - Martinus Aripin; Silpanus Silpanus (Sekolah Tinggi Kateketik Pastoral Katolik (STKPK) Bina Insan Keuskupan Agung Samarinda, 2022)
Religion and culture are central to building harmonious relations between adherents of different religions. This study aims to explore the values of moderation in the religious moderation tradition of the Dayak Aoheng tribe's harvest thanksgiving tradition in Tiong Ohang Village, Long Apari District, Mahakam Ulu District. This study uses a qualitative approach to reveal empirical data facts related to people's lives and cultural traditions, especially Aoheng. The data collection method related to the values of religious moderation in the tradition of harvest thanksgiving for the Dayak Aoheng community uses a combination of several complementary methods, namely: (1) collection of written documents on the rice thanksgiving tradition from previous researchers and writers; (2) collection of photographic and recorded documents regarding the rice harvesting traditions of the Aoheng people which can be accessed from various sources; and 3) interviews with informants. This study involved three indigenous informants who understood the harvest thanksgiving tradition of the Aoheng people. The data collected was analyzed descriptively to describe the values of religious moderation in the Aoheng community's harvest thanksgiving tradition. The results of this study conclude that moderate religious practices are internalized in the local wisdom values of the Aoheng community's harvest thanksgiving tradition, namely kinship, togetherness, and tenacity.